The righteous mind : why good people are divided by politics and religion - Haidt, Jonathan (New York : Pantheon Books, 2012)
A groundbreaking investigation into the origins of morality, which turns out to be the basis for religion and politics. The book explains the American culture wars and refutes the "New Atheists."
Where does morality come from? -- The intuitive dog and its rational tail -- Elephants rule -- Vote for me (here's why) -- Beyond WEIRD morality -- Taste buds of the righteous mind -- The moral foundations of politics -- The conservative advantage -- Why are we so groupish? -- The hive switch -- Religion is a team sport -- Can't we all disagree more constructively?
Includes bibliographical references and index.
Keywords: Ethics; Social psychology; Political psychology; Psychology, Religious